A Natural Alkaloid, 6-Hydroxymethyldihydronitidine, Suppresses Tumor Progression by Co-Regulating Apoptosis, Ferroptosis, and FAK Pathways - Haojing Jiang; Jiantong Hou; Jianliang Wang; Jing Xu; Yuanqiang Guo (Biomolecules, 2025)
Cancer treatment remains a formidable challenge globally. Natural products, particularly natural alkaloids, have emerged as significant resources for the development of novel anti-tumor drugs due to their structural diversity and unique biological activities. Our team previously isolated an alkaloid, 6-hydroxymethyldihydrochelerythrine (6-HMDN), from Zanthoxylum ailanthoides. Subsequent in vitro and in vivo activity screenings, utilizing cell-based assays and a zebrafish xenograft model, revealed that 6-HMDN significantly inhibited the proliferation of HepG2 and MCF7 cells and effectively suppressed HepG2 cell migration. Mechanistic studies indicated that 6-HMDN induced tumor cell apoptosis by modulating the Bcl-2/Bax protein balance and activating the caspase cascade. Furthermore, 6-HMDN augmented intracellular reactive oxygen species (ROS) levels, thereby promoting ferroptosis, as evidenced by lipid ROS accumulation and glutathione (GSH) depletion. Additionally, 6-HMDN attenuated focal adhesion kinase (FAK) phosphorylation, leading to the inhibition of tumor cell migration. In vivo experiments further substantiated the capacity of 6-HMDN to effectively suppress tumor proliferation and metastasis. These findings demonstrate that 6-HMDN exhibits potent anti-tumor activity, exerting its effects through multiple mechanisms involving the regulation of apoptosis, ferroptosis, and the FAK signaling pathway. Therefore, 6-HMDN may be considered a promising candidate for anti-tumor drug development.